PROFILING VOCABULARY OF ENGLISH TEXTBOOKS FOR INDONESIAN JUNIOR HIGH SCHOOLS USING VOCABULARY PROFILER: A FAST TRACK TO IMPROVE STUDENTS’ VOCABULARY KNOWLEDGE - Gusti Astika (IJOTL-TL: Indonesian Journal of Language Teaching and Linguistics, 2016)
This research analyzed vocabulary profile used in one series of English textbooks currently used in Indonesian Junior High School. The sample text books were: When English Rings a Bell for grades VII, VIII, and Think Globally Act Locally for grade IX. These books have been recommended by the Ministry of Education and Culture for use in Indonesian Junior High Schools. This research used Classic Vocabulary Profileras a tool to profile vocabulary in the text books. The overall profile shows that vocabulary coverage of the most frequently used words (K1 and K2) was 92.65%, indicating that it is below the necessary level (95%) for easy comprehension. The analysis also reveals  negative vocabulary profile, that is proportions of word families in K1 and K2 groups that were not found in the text books. This study recommends to improve the text book comprehensibility.